Let It Go: Lingering Negative Affect in Response to Daily Stressors Is Associated With Physical Health Years Later - Leger, Kate A.; Charles, Susan T.; Almeida, David M. (Psychological Science, 2018)
The way we respond to life’s daily stressors has strong implications for our physical health. Researchers have documented the detrimental effects of initial emotional reactivity to daily stressors on future physical health outcomes but have yet to examine the effects of emotions that linger after a stressor occurs. The current study investigated how negative affect that lingers the day after a minor stressor occurs is associated with health-related outcomes. Participants ( N = 1,155) in a community-based, nationwide study answered questions about daily stressors and affect across 8 consecutive days and about their physical health almost 10 years later. Multilevel models indicated that people experience heightened levels of negative affect the day after a stressor occurs. Furthermore, higher levels of lingering negative affect are associated with greater numbers of chronic conditions and worse functional limitations 10 years later. Findings suggest that affective recovery from daily stressors has unique importance for long-term physical health.